Pengaruh Bauran Promosi terhadap Minat Beli dengan Mediasi Brand Image - Tan, Kevin; Utami, Christina Whidya; Vidyanata, Deandra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The economic growth of the food and beverage industry in East Java keeps on increasing. In 2018, Cikake was established in Surabaya, offering rice-bowl as its main product. Since 2019 Cikake has had its first outlet at a food court called Foodland Pandaan, in Pandaan, East Java. Cikake has a commitment in which every two years will open several offline stores or outlets starting from several cities around Surabaya. During two years running, Cikake's sale turnover has always fluctuated, which has drives Cikake to do promotional activities to improve Cikake's brand image and purchase intention of Cikake consumer. This research aims to determine the effect of promotional mix on purchase intention, the effect of promotional mix on brand image, the effect of brand image on purchase intention, and the effect of promotional mix on purchase intention by mediating brand image. This type of research is quantitative. The population in this research is people who have an interest in Cikake product. The sample consists of 190 respondents using the purposive sampling technique. Data analysis in the research uses Partial Least Square with SmartPLS 3.0 program to calculate data. This research indicates that brand image significantly mediates the effect of promotional mix on purchase intention. Likewise, the promotional mix significantly affects brand image. Also, promotional mix and brand image significantly affect purchase intention.